(untitled) (Heritage, 2025)
The main aim of the paper is to explore the modalities within which Isidora Sekulić shapes her conception of the (Serbian) national community, its historical dynamics and foundations, as well as the way in which she interprets its past and cultural and political heritage. By interpreting essays written in the interwar period, we will attempt to shed light on the author’s immersion in or distance from the historically current moment, as well as the peculiarities that appear in her thought system, which are recognized as different in comparison to essays from the beginning of the second decade of the 20th century. An analysis of earlier essays has shown the author’s constant movement between culture and combativeness as possible principles that would ensure national freedom. The liberation of Serbian territories achieved during the First and Second Balkan Wars, as well as the First World War, led to an expansion of the observed horizon, which will be visible in the interwar essays primarily through the problematization of the term small people, the conceptualization of the term racial and breakthroughs into the Balkanist discourse.